Determinants of Quiet Quitting among Generation Z Employees: The Mediating Effect of Employee Well-Being - Asyip Abdul Mu’iz Annasihi; Muhammad Irfan Syaebani (Research Horizon, 2026)
In the logistics industry’s transformation, human resource challenges have emerged as quiet quitting, particularly among Generation Z workers. This study aims to analyze the influence of quiet firing, perceived organizational support, and psychological capital on quiet quitting levels, with employee well-being as a mediating variable. This study employs a quantitative approach, using a sample of 300 permanent Generation Z employees in port service companies selected through purposive sampling. Data were analyzed using covariance-based SEM with LISREL 8.80. The results show that quiet firing has a significant positive effect on quiet quitting behavior through the mechanism of eroding employees’ psychological resources. Conversely, perceived organizational support and psychological capital are proven to have a positive influence on enhancing employee well-being. A significant finding in this study indicates that psychological capital does not have a direct effect on suppressing quiet quitting, but rather through partial mediation by employee well-being. Furthermore, psychological capital is proven to be the strongest personal factor capable of mitigating quiet quitting tendencies. These findings imply that port management needs to integrate managerial transparency with psychological capacity building to achieve performance sustainability within the global logistics chain.